The Effect of Online to Offline (O2O) Services Through Mobile Apps in Indonesian Coffee Shop towards Consumers Purchase Decision - Iisnawati Iisnawati; Aslamia Rosa; Welly Nailis (University of Merdeka Malang, 2024)
The surge of Online to Offline (O2O) mobile applications in the Food & Beverage (F&B) industry has become a significant trend, particularly in the wake of the COVID-19 pandemic. This study aims to empirically investigate the substantial impact of various consumption values on consumer purchase decisions when utilizing O2O mobile apps, a trend that has gained considerable momentum within the modern coffee industry. The urgency of this research is underscored by the growing prevalence of O2O purchases through mobile applications, specifically in contemporary coffee establishments. Data for this study were meticulously gathered through questionnaires administered to 200 users of O2O mobile applications from modern coffee shops, employing non-probability sampling techniques. The analysis was conducted using multiple linear regression with SPSS software. The findings reveal that several factors, including Prestige Value, Enjoyment, Affordance Value, and Visibility Value, significantly influence consumer purchase decisions at modern coffee shops in Palembang. Interestingly, Price Value did not show a significant impact on consumer decisions within these establishments in Palembang. This study highlights the evolving dynamics of consumer behavior in the context of O2O mobile app usage in the F&B sector, emphasizing the importance of specific consumption values that drive purchase decisions, thereby offering crucial insights for businesses aiming to enhance their O2O strategies.